Contribution of galactoglycerolipids to the 3‐dimensional architecture of thylakoids. Issue 8 (15th April 2014) - Demé, Bruno; Cataye, Céline; Block, Maryse A.; Maréchal, Eric; Jouhet, Juliette
Abstract : Thylakoid membranes, the universal structure where photosynthesis takes place in all oxygenic photosynthetic organisms from cyanobacteria to higher plants, have a unique lipid composition. They contain a high fraction of 2 uncharged glycolipids, the galactoglycerolipids mono‐ and digalactosyldiacylglycerol (MGDG and DGDG, respectively), and an anionic sulfolipid, sulfoquinovosediacylglycerol (SQDG). A remarkable feature of the evolution from cyanobacteria to higher plants is the conservation of MGDG, DGDG, SQDG, and phosphatidylglycerol (PG), the major phospholipid of thylakoids. Using neutron diffraction on reconstituted thylakoid lipid extracts, we observed that the thylakoid lipid mixture self‐organizes as a regular stack of bilayers. This natural lipid mixture was shown to switch from hexagonal II toward lamellar phase on hydration. This transition and the observed phase coexistence are modulated by the fine‐tuning of the lipid profile, in particular the MGDG/DGDG ratio, and by the hydration. Our analysis highlights the critical role of DGDG as a contributing component to the membrane stacking via hydrogen bonds between polar heads of adjacent bilayers. DGDG interactions balance the repulsive electrostatic contribution of the charged lipids PG and SQDG and allow the persistence of regularly stacked membranes at high hydration. In developmental contexts or in response to environmental variations, these properties can contribute to the highly dynamic flexibility of plastid structure.—Demé, B., Cataye, C., Block, M. A., Maréchal, E., Jouhet, J. Contribution of galactoglycerolipids to the 3‐dimensional architecture of thylakoids. FASEB J. 28, 3373–3383 (2014). www.fasebj.org